Medicine beyond borders: legal and ethical challenges - Jahn Kassim, Puteri Nemie (World Associatio For Medical Law, 2009)
The ease and affordability of international travel has contributed to the rapid growth of the healthcare industry where people from all around the world are traveling to other countries to obtain medical, dental, and surgical care while at the same time touring, vacationing and fully experiencing the attractions of the countries that they are visiting. A combination of many factors has led to the recent increase in popularity of medical tourism such as exorbitant costs of healthcare in industrialized nations, favorable currency exchange rates in the global economy, rapidly improving technology in many countries of the world and most importantly proven safety of healthcare in selected foreign nations. Nevertheless, the development of medical tourism has certainly awakened many ethical and legal issues, which must be addressed. Issues pertaining to malpractice, consumer protection, organ trafficking, alternative medicine and telemedicine need comprehensive legal regulatory framework to govern them. Ethical issues are also been raised by the promotion of medical tourism in particular those pertaining to doctor and patient relationship. A future, where medical law is subsumed into various legal and ethical dimensions, poses serious challenges for the practice and ethics of medicine.